An evaluation of dried blood spots and oral swabs as alternative specimens for the diagnosis of dengue and screening for past dengue virus exposure - Anders, K; Nguyet, N; Quyen, N; Ngoc, T; Tram, T; Gan, T; Tung, N; Dung, N; Chau, N; Wills, B; Simmons, C (American Society of Tropical Medicine and Hygiene, 2012)
Non-invasive specimens for dengue diagnosis may be preferable where venous blood is difficult to collect and/or process, such as community-based or remote settings or when sampling from young children. We evaluated the performance of oral swabs and dried blood spots (DBS), compared with plasma, in diagnosing acute dengue and screening for past dengue virus (DENV) exposure. DENV-specific immunoglobulin (Ig) M, IgG, and NS1 antigen were detected both in oral swabs and DBS from acute patients. Oral swabs were less sensitive (IgM: 68.7%, IgG: 91.9%, NS1: 64.7%), but retained good specificity (100%, 92.3%, 95.8%, respectively) compared with plasma. DBS displayed high sensitivity (IgM: 100%, IgG: 96%, NS1: 100%) and specificity (IgM: 75%, IgG: 93%). DENV RNA was amplified from DBS (sensitivity 95.6%) but not from oral swabs. DENV-IgG (indicative of past flavivirus exposure) were detected with moderate sensitivity (61.1%) but poor specificity (50%) in oral swabs from healthy volunteers. Dried blood spots allow sensitive and specific diagnosis of acute dengue by serological, molecular, and antigen detection methods. Oral swabs may be an adequate alternative where blood cannot be collected.